A tritrophic interaction model for an olive tree pest, the olive moth - Prays oleae (Bernard) - Pappalardo, Sonia (2022)
The olive tree (Olea europaea L.) is among the oldest and most widespread crops in the Mediterranean basin. Portugal is the third olive producer in the European Union, and Trás-os-Montes region, located in northeastern Portugal, is the second Portuguese producing olive region. The olive moth, Prays oleae (Bernard) (Lepidoptera: Praydidae) is a key olive pest in Trás-os-Montes. This pest is a natural host/prey of several organisms which include larvae of generalist and specialist parasitoids as well as generalist predators and entomopathogens. Its most abundant parasitoid is the specialist Ageniaspis fuscicollis (Dalman) (Hymenoptera: Encyrtidae) and this, in Trás-os-Montes region, is commonly followed by the facultative hyperparasitoid Elasmus flabellatus (Fonscolombe) (Hymenoptera: Eulophidae). Spiders represent a relevant group of generalist predators in olive agroecosystems and encompass an important predatory action in agroecosystems as well as an ability to reduce the populations of various insect pests. In this context, a mathematical model, considering the population of the olive moth, the two parasitoids populations and the spider population as the variables in our system, was constructed. The ecosystem steady states for feasibility and stability were assessed. The possible pesticide effects, that represent essentially extra mortality rates for each one of the insect populations, and potential abundance variations on their populations under a climate change scenario were included. Results indicate that the most important natural control agent is A. fuscicollis but in certain conditions E. flabellatus or spiders may be relevant contributors for the pest reduction. This approach may provide a useful tool to assist the field researchers on this pest system and its management